Prevalence factors associated with equine herpesvirus type 1 infection in equids with upper respiratory tract infection and/or acute onset of neurological signs from 2008 to 2014. (16th January 2016) - Pusterla, N.; Mapes, S.; Akana, N.; Barnett, C.; MacKenzie, C.; Gaughan, E.; Craig, B.; Chappell, D.; Vaala, W.
Abstract : The objective of the present case‐control study was to determine prevalence factors associated with the detection of equine herpesvirus type 1 (EHV‐1) by quantitative PCR (qPCR) in horses presented to veterinarians with clinical signs related to an upper respiratory tract infection and/or acute onset of neurological disease from March 2008 to December 2014. Nasal secretions and whole blood from 4228 equids with acute onset of fever, respiratory signs and/or neurological deficits were tested by qPCR for EHV‐1. Categorical analyses were performed to determine the association between observations and EHV‐1. A total of 117/4228 (2.7 per cent) equids tested qPCR‐positive for EHV‐1, with most of the isolates belonging to the non‐neuropathogenic genotype (N752 ). EHV‐1 PCR‐positive equids were over‐represented in racing horses. Depression, anorexia, nasal discharge and coughing were significantly less frequently reported in the EHV‐1 qPCR‐positive equids compared with the EHV‐1 qPCR‐negative cases. Neurological deficits were more frequently reported in the EHV‐1 qPCR‐positive cases. This study provides contemporary information on the frequency of EHV‐1 detection by qPCR in blood and nasal secretions from horses with fever, respiratory signs and neurological deficits.